Modular Decomposition Method Based on Design Structure Matrix and Application - Mengqi Li; Dongying Li (Indonesian Journal of Electrical Engineering and Computer Science, 2012)
Modular decomposition is an effective means to achieve a complex system, but that of current part-component-based does not meet the needs of the positive development of the production. Design Structure Matrix(DSM) can simultaneously reflect the sequence, iteration, and feedback information, and express the parallel, sequential, and coupled relationship between DSM elements. This article, a modular decomposition method, named Design Structure Matrix Clustering modularize method, is proposed, concerned procedures are define, based on sorting calculate and clustering analysis of DSM, according to the rules of rows exchanges and columns exchange with the same serial number. The purpose and effectiveness of DSM clustering modularize method are confirmed through case study of assembly and calibration system for the large equipment. DOI: http://dx.doi.org/10.11591/telkomnika.v10i8.1656